Myasthenia gravis in clinical practice - Eduardo de Paula Estephan; José Pedro Soares Baima; Antonio Alberto Zambon (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Myasthenia gravis is largely a treatable disease, but it can result in significant morbidity and even mortality, which can usually be avoided, or at least mitigated, with timely diagnosis and appropriate treatment of the disease. Objective: this review aims to summarize the main practical aspects of the diagnostic approach, treatment and care of myasthenic patients. Methods: The authors performed a non-systematic critical review summarizing the main practical aspects of myasthenia gravis. Results: Most patients with myasthenia have autoantibodies targeted at acetylcholine receptors or, less commonly, muscle-specific kinase - MuSK. Electrophysiology plays an important role in the diagnosis of neuromuscular junction dysfunction. The central clinical manifestation of myasthenia gravis is fatigable muscle weakness, which can affect eye, bulbar, respiratory, and limb muscles. With rare exceptions, patients have a good response to symptomatic treatment, but corticosteroids and/or immunosuppressants are usually also necessary to obtain good control of the manifestations of the disease. Conclusion: Knowledge of the peculiar aspects of their clinical and electrophysiological presentations is important for the diagnosis. Likewise, specific treatment and response time to each drug are crucial for proper care.